Teacher Communication In Bruneian Secondary Science Classes: Wait-Time - S. Dhindsa, Harkirat (Penerbit Universiti Sains Malaysia, 2010)
A study was undertaken to (a) explain the wait-time that reflects the cognitive processes involved in the construction and reconstruction of knowledge in interpreting questions and then providing responses and (b) compare the mean wait-time taken by students with the wait-time intended by teachers, in both theory and practical classes in Bruneian secondary schools. The recorded wait-time was explained using the construction and reconstruction model of human learning proposed by Anderson and Demetrius (1993). Wait-time differences between the theory and practical classes were found to be statistically significant. There was also a significant variation in the waittime for three different categories of response to the questions – viz. responses by the whole class, an individual student, and the teacher. The mean wait-time data recorded in this study resembles that previously reported elsewhere. However, the wait-time for nonbilingual Bruneian students learning science in a second language includes a component for language translation, which occurs during both the knowledge construction and reconstruction phases. Further research is recommended to (a) evaluate the optimum wait-time under the conditions that prevail in Bruneian science classes and (b) modify the existing information-processing model or to develop new models to explain knowledge construction and reconstruction in classes where non-bilingual students learn science in a second language.